“Social Security” bagi Tenaga Kerja Informal pada Sektor Industri Ekstraktif di Bojonegoro - Ahmad Sholikin (Universitas Islam Darul Ulum Lamongan, 2024)
This research addresses considerations when designing and implementing social protection programs and systems for informal sector workers in the extractive industry in Bojonegoro Regency. Policy and program considerations relating to social protection, the quality of day-to-day administration of social protection programs greatly influence the extent to which these programs generate the expected impact. This paper outlines best practices at each level of social protection program design and implementation as a way to provide guidance on how such programs can best meet the needs of informal sector workers. As such, it also includes examples of social protection programs and systems that address the vulnerabilities faced by informal sector workers in extractive industries in other countries and regions. The aim is to explore the level of access and understanding of informal workers to social protection programs in the extractive industry sector in Bojonegoro. The research methods used include surveys and interviews with a representative sample of informal workers in the sector. The main findings of this study show that the level of access to social protection, such as health insurance and social security, is still low among informal workers. In addition, their understanding of social rights and the availability of social protection programs is also limited. These results highlight the need for greater efforts from the government and other stakeholders to improve informal workers' awareness and access to social protection. Policy implications of this study include expanding the coverage of social protection programs, improving accessibility and understanding of these programs, and developing more inclusive policies to improve the welfare of informal workers in the extractive industry sector in Bojonegoro.